2003
DOI: 10.1128/jvi.77.7.4383-4388.2003
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Cells, Including Macrophages, Are Prominent in Theiler's Virus-Induced Inflammatory, Demyelinating Lesions

Abstract: Theiler's murine encephalomyelitis virus (TMEV) persists in the mouse central nervous system principally in macrophages, and infected macrophages in culture undergo apoptosis. We have detected abundant apoptotic cells in perivascular cuffs and inflammatory, demyelinating lesions of SJL mice chronically infected with TMEV. T cells comprised 74% of apoptotic cells, while 8% were macrophages, 0.6% were astrocytes, and ϳ17% remained unidentified. In situ hybridization revealed viral RNA in ϳ1% of apoptotic cells.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…This form of cell death has been of interest with respect to TMEV because of the marked difference in virulence and persistence manifested by strains of the two subgroups of TMEV: GDVII and other members of the GDVII subgroup are highly virulent, causing a fatal acute disease with no virus persistence, while DA, BeAn, and other members of the TO subgroup cause a chronic, progressive demyelinating disease in which virus routinely persists in the CNS for the life of the mouse. Apoptosis has been reported both in the acute disease caused by DA and GDVII virus and during chronic TMEV-IDD (2,5,20,26). A number of different cell types have been found to undergo apoptosis, including activated macrophages/microglia, T cells, and oligodendrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This form of cell death has been of interest with respect to TMEV because of the marked difference in virulence and persistence manifested by strains of the two subgroups of TMEV: GDVII and other members of the GDVII subgroup are highly virulent, causing a fatal acute disease with no virus persistence, while DA, BeAn, and other members of the TO subgroup cause a chronic, progressive demyelinating disease in which virus routinely persists in the CNS for the life of the mouse. Apoptosis has been reported both in the acute disease caused by DA and GDVII virus and during chronic TMEV-IDD (2,5,20,26). A number of different cell types have been found to undergo apoptosis, including activated macrophages/microglia, T cells, and oligodendrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…During TMEV-IDD, apoptosis of T cells, microglia/macrophages, and oligodendrocytes has been described (2,5,20,26). In vitro studies have implicated the cardiovirus L protein, which is encoded between the start of the polyprotein and the P1 capsid proteins (Fig.…”
mentioning
confidence: 99%
“…BeAn virus persists primarily in macrophages in the CNS of infected mice. Schlitt et al (34) found that 74% of TUNEL-positive cells in infected spinal cords (primarily in CNS lesions) were T and B lymphocytes and 8% were macrophages, although virus genomes were detected in Ͻ1% of apoptotic cells, consistent with infection of only a low percentage of macrophages and the fact that TMEV does not infect T or B lymphocytes in culture. Thus, some means other than direct infection was responsible for apoptosis of most CNS macrophages, including TMEV triggering apoptosis through tumor necrosis factor alpha or tumor necrosis factor alpha-related apoptosis-inducing ligand by binding death receptors on activated macrophages in vitro, as reported elsewhere (17).…”
mentioning
confidence: 99%
“…However, virus-specific T cells, various proinflammatory chemokines (e.g., monocyte chemoattractant protein 1 and interferon-inducible protein 10), and cytokines (e.g., gamma interferon [IFN-␥] and tumor necrosis factor alpha) in the central nervous system (CNS) are believed to play a critical role (reviewed in references 26 and 44) in this disease process. In addition, the presence of persistent viral infection may lead to demyelinating disease by directly causing host cell lysis (51), which releases sequestrated CNS autoantigens, resulting in the activation of autoreactive T cells (39). The persistence of viral antigens also is believed to perpetuate a massive inflammatory milieu in the CNS by continuously activating virus-specific T cells (25,33).…”
mentioning
confidence: 99%